The phototransformations of trans-stilbene and its derivatives on laser excitation - Samsonova, Lyubov G.; Kopylova, Tatyana N.; Svetlichnaya, N. N.; Andrienko, O. S. (High energy chemistry)
The photostability of solutions of trans-stilbene and its derivatives on excitation with an XeCl excimer laser was studied. The quantum yield of phototransformations was found to depend on the intensity of exciting light; namely, the compounds had higher photostability in more intense excitation ﬁelds. This fact was explained by competition between the processes of photoisomerization and stimulated emission.